Performance analysis of hybrid renewable energy systems used for rural electrification in Malaysia / Laith Mahmoud Mohammad Halabi - Laith Mahmoud, Mohammad Halabi (2017)
Finding the sustainable, reliable and environmentally-friendly source of energy for remote areas is regarded as one of the major issues in the last decade. However, extending the national grid considered as economically impractical or sometimes technically impossible due to harsh geographical terrains and dispersed population. Normally, such areas are used standalone diesel generators to supply electrical power, which partially covers the load demand. Such standalone systems suffer from several problems of transporting and storing the fuel beside discontinues operation due to maintenance concerns. The alternative solution to solve these issues is to establish hybrid energy system contains; conventional and renewable energy sources with or without storage system. These systems have received greater attention in recent years, where many studies have performed to find the optimal design without analyzing the operational performance. Analyzing the operational data and performance metrics of two hybrid PV/diesel hybrid systems remotely located in Sabah – Malaysia at (Pulau Banggi and Tanjung Labian) are considered throughout this work. We first verified the collected data followed by the development of all possible scenarios of standalone diesel generators, existing hybrid PV/diesel/battery and 100% PV/batteries systems. Also, developing the optimum systems in both sites is also performed. The analysis examined the performance based on technical, economic and environmental aspects. Furthermore, the development of solar radiation prediction algorithms in addition to integrating a flexible hybrid renewable energy design are presented. HOMER software and MATLAB are used in this work. The comparison of the existing systems with the optimized scenarios indicates that the existing systems have not optimally selected prior installation. Where the existing hybrid PV/diesel/battery system shows the best performance compared to standalone diesel generators and 100% PV/batteries scenarios in terms of the technical aspects as well as supporting 24-hour energy access. Meanwhile, the standalone diesel generator system shows the best economic scenario. The inclusion of RE resources in power generation has resulted in improving the system performance and minimizing the dependence on fossil fuel and reducing the generated amount of harmful emissions towards the surrounding environment as well. It also resulted in increasing system sustainability. Accordingly, the results of predicting monthly global solar radiation showed a very good agreement between the predicted and measured data sets besides it demonstrated the high prediction capability of the developed hybrid models using standalone Adaptive Neuro-Fuzzy Inference System (ANFIS) and hybrid ANFIS models which include ANFIS-PSO (Particle Swarm Optimization), ANFIS-GA (Genetic Algorithm), and ANFIS-DE (Differential Evolution). The developed modules showed high accuracy in the prediction of solar radiation. In addition, it is considered as an effective tool in predicting solar radiation and deemed to be suitable for further use in various engineering and practical applications. Furthermore, the proposed flexible design is verified over different combinations and indicated the high capability in meeting the loads, support continuous operation and reduce the harmful emissions towards the environment overall conditions for both off-grid and on-grid connections. Besides, showing the importance of including storage system (batteries) to store excess energy and reducing the losses in the off-grid connections. An accurate analysis of the operational performance of hybrid renewable energy stations would enhance the optimal planning and designing of new projects around the world.